2017
DOI: 10.1075/lab.15026.ant
|View full text |Cite
|
Sign up to set email alerts
|

Language performance of sequential bilinguals on an Irish and English sentence repetition task

Abstract: Currently there are no standardized language assessments for English-Irish bilingual school age children that would test languages in a comparable way. There are also no standardized language assessments of Irish for this age group. The current study aimed to design comparable language assessments in both languages targeting structures known to be challenging for children with language impairments. A sentence repetition (SRep) task equivalent to the English SRep task (Marinis, Chiat, Armon-Lotem, Piper, & … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Furthermore, bilingual children scored lower on syntax as compared to their monolingual peers. This is in line with previous studies showing that bilingual children score lower on SRep tasks when compared to monolingual peers (Antonijevic et al, 2017; Fleckstein et al, 2018; Komeili & Marshall, 2013; Meir, 2017; among many others). Yet, similarly to previous research (Komeili & Marshall, 2013; Meir, 2017), our study showed that the negative effect of bilingualism disappeared once vocabulary scores were controlled for.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, bilingual children scored lower on syntax as compared to their monolingual peers. This is in line with previous studies showing that bilingual children score lower on SRep tasks when compared to monolingual peers (Antonijevic et al, 2017; Fleckstein et al, 2018; Komeili & Marshall, 2013; Meir, 2017; among many others). Yet, similarly to previous research (Komeili & Marshall, 2013; Meir, 2017), our study showed that the negative effect of bilingualism disappeared once vocabulary scores were controlled for.…”
Section: Discussionsupporting
confidence: 92%
“…As for bilingual children, previous studies found that bilinguals with TLD have lower syntactic abilities compared to monolingual children with TLD, as measured by SRep tasks (Antonijevic, Durham, & Chonghaile, 2017; Fleckstein, Prévost, Tuller, Sizaret, & Zebib, 2018; Komeili & Marshall, 2013; Meir, 2017). Yet, this negative effect of bilingualism on SRep tasks disappears when vocabulary scores are controlled for (Komeili & Marshall, 2013; Meir, 2017).…”
Section: Introductionmentioning
confidence: 98%
“…Another set of studies using LITMUS-SR tasks investigated TD bilingual children with the goal of addressing both the differences between the children's L1 and L2 and the effects of internal and external factors on the children's performances. Antonijevic et al (2017) designed an Irish LITMUS-SR task and used it with bilingual children with English as L1 and Irish as L2. The English and the Irish tasks included sentences that were grouped around three levels of complexity and measured different sentence structures and types of errors.…”
Section: Using Sr Tasks With Bilingual Childrenmentioning
confidence: 99%
“…Sentence Repetition tasks are widely used to assess morpho-syntactic abilities of monolingual and bilingual children. Sentence Repetition tasks have been shown to be highly effective in discriminating children with typical and atypical language development in monolingual and bilingual populations (e.g., Conti-Ramsden et al, 2001 ; Archibald and Joanisse, 2009 ; Klem et al, 2015 ; Meir et al, 2016 ; Antonijevic et al, 2017 ; Gavarró, 2017 ; Hamann and Abed Ibrahim, 2017 ; Theodorou et al, 2017 ; Fleckstein et al, 2018 ; among many others). In the following subsections, quantitative and qualitative characteristics of the Weaker Language of unbalanced bilinguals are discussed as compared to BB and unbalanced bilinguals in the Dominant Language.…”
Section: Introductionmentioning
confidence: 99%